Fenomena Komunikasi Kaum Gay di Era Digital - SIDABALOK, ROBET; Telussa, Sandra (Jurnal Ilmu Komunikasi Pattimura, 2022)
Deviant sexual orientation makes it difficult for gays to interact and communicate like a dominant society, this makes gays need an alternative media in order to interact and communicate with the aim of meeting their social and sexual needs. Gays also use blued applications to meet these needs. This study aims to determine the phenomenon of gay communication on the blued application in the city of Ambon. The theoretical basis used in this research is the theory of social penetration and computer mediated communication (CMC). This research is a qualitative descriptive study with an individual unit of analysis, namely gay people who use the blued application. This study uses data collection techniques in the form of interviews with six resource persons, participatory observation, and documentation. Data analysis techniques used in this study were data reduction, data presentation, conclusion drawing and data triagulation. The results of this study indicate that gay users of the Blued application in Ambon City have different goals and ways when using the application to fulfill their personal needs. gay people also have different special criteria when they start a communication with each other in the application. So it is undeniable that technology-mediated communication is very helpful for gay people to be able to interact and communicate with each other. Although to improve relationships, it must still be done with several other supporting social media platforms in order to create better relationships. Based on the results of the study, mediated communication is very helpful in meeting the needs of gay people, but the communication that exists between gay people face to face is still the final achievement of developing a relationship that has been built for the better.